ПСИХОЛОГО-ПЕДАГОГІЧНЕ УПРАВЛІННЯ АКТИВНІСТЮ УЧНІВ ЯК ФОРМА РОЗВИТКУ СОЦІАЛЬНО ЗНАЧУЩИХ ЯКОСТЕЙ ОСОБИСТОСТІ ШКОЛЯРА (Педагогіка вищої та середньої школи, 2007)
The article investigates the influence of psychological and pedagogical guidance of students’ activity in terms of developing qualities which are socially important for a personality.